Navarro Baldeweg: Installation and infrastructure in Canal de Castilla - García-Germán Vázquez, Jacobo (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2023)
The action of re-describing, by means of looking, registering and re-presenting a pre-existing reality, updating its content and transforming it into operational material, has been constituted in recent decades as a specific architectural project technique. A technique endowed with its own genealogy and unique disciplinary tools. In the contemporary context of energy crisis, oversaturation of the built world and the need to creatively reevaluate the different inherited historical heritages, minimal intervention resources and the ability of architecture to lighten up, with a new perspective, an as-found scenario, acquire prominence as mechanisms of action for the architect.The work on the disused fluvial infrastructure of the Canal de Castilla carried out in the academic context of the Escuela Técnica Superior de Arquitectura de Madrid by the architect and artist Juan Navarro Baldeweg in 1980-82, is a convenient case study as an early contribution to these procedures. A collective architectural process associated with mechanisms derived from the artistic avant-gardes of that moment, as well as with a pioneering sensitivity in the reconsideration of industrial heritage, while acting as a field of conceptual experimentation for subsequent architectures by Navarro Baldeweg. The text studies this process and its interweaving with the academic, architectural and transdisciplinary lines that support it.
Keywords: Navarro Baldeweg; Canal de Castilla; infrastructure; installation; drawing; gaze